Math, factoring

Two of the roots of x^4 +ax^3 +ax^2+11x+b=0 are 3 and -2.

1. Find the value of a and b

2. Find the other roots.


I believe that a = -3 and b = -6.
I am unsure of how to find the other roots.

Please show how you found the answer.

asked by Adeline

  1. For x = 3

    x ^ 4 + a x ^ 3 + a x ^ 2 + 11 x + b = 0

    Put x = 3 in this equation:

    3 ^ 4 + a * 3 ^ 3 + a * 3 ^ 2 + 11 * 3 + b = 0

    81 + 27 a + 9 a + 33 + b = 0

    36 a + b + 114 = 0


    For x = - 2

    x ^ 4 + a x ^ 3 + a x ^ 2 + 11 x + b = 0

    Put x = - 2 in this equation:

    ( - 2 ) ^ 4 + a * ( - 2 ) ^ 3 + a * ( - 2 ) ^ 2 + 11 * ( - 2 ) + b = 0

    16 - 8 a + 4 a - 22 + b = 0

    - 4 a + b - 6 = 0


    Now you must solve system:

    36 a + b + 114 = 0

    - 4 a + b - 6 = 0

    The solutions are: a = - 3 , b = - 6

    So equation x ^ 4 + a x ^ 3 + a x ^ 2 + 11 x + b = 0 becomes:

    x ^ 4 - 3 x ^ 3 - 3 x ^ 2 + 11 x - 6 = 0


    We can take a polynomial of degree 4, such as:

    ( x - p ) ( x - q ) ( x - r ) ( x - s )

    where: p , q , r , s are roots of polynomials

    In this casse you know two roots : p = 3 and q = - 2

    Now ( x - p ) ( x - q ) ( x - r ) ( x - s ) becomes:

    ( x - 3 ) [ x - ( - 2 ) ] ( x - r ) ( x - s ) =

    ( x - 3 ) ( x + 2 ) ( x - r ) ( x - s ) =

    ( x ^ 2 - x - 6 ) ( x - r ) ( x - s ) = 0

    If

    x ^ 4 - 3 x ^ 3 - 3 x ^ 2 + 11 x - 6 = ( x ^ 2 - x - 6 ) ( x - r ) ( x - s )

    then you must do long division:

    ( x ^ 4 - 3 x ^ 3 - 3 x ^ 2 + 11 x - 6 ) / ( x ^ 2 - x - 6 ) = x ^ 2 - 2 x + 1

    This mean ( x - r ) ( x - s ) = x ^ 2 - 2 x + 1

    If ( x - r ) ( x - s ) = 0 then x ^ 2 - 2 x + 1 also = 0

    x ^ 2 - 2 x + 1 = 0

    Solution: x = 1

    Or:

    x ^ 2 - 2 x + 1 = ( x - r ) ( x - s ) = ( x - 1 ) ( x - 1 )

    Factors of your polynomial:

    x ^ 4 - 3 x ^ 3 - 3 x ^ 2 + 11 x - 6 = ( x - 3 ) ( x + 2 ) ( x - 1 ) ( x - 1 )

    All this mean:

    Your polynomialal have 3 roots:

    x = - 2 , x = 3 and a double root x = 1





    posted by Bosnian
  2. Divide by (x^2-x-6) and you get
    quotient: x^2+(a+1)x+(2a+7)
    remainder: (8a+24)x + b+6(2a+7)

    For the remainder to be zero, we need

    a = -3
    b = -6

    So, x^4-3x^3-3x^2+11x-6
    = (x+2)(x-3)(x^2-2x+1)

    The other roots are 1,1

    posted by Steve

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    Find all integer roots of f(x). Identify any double roots. f(x) = 2x4 + 11x3 + 13x2 - 11x - 15
  2. algebra

    find a third degree polynomial equation with coefficients that has roots -4 and 6+i possible answers x^3-8x^2-11x+148=0 x^3-8x^2-12x+37=0 x^3-12x^2+37x=0 x^3-8x^2-11x=0
  3. Math

    State the number of complex roots,possible number of real roots and possible rational roots for x^5 - x^3 - 11x^2+ 9x+18=0
  4. Algerbra 2

    find the possible roots for: 3x^3-6x^2+11x-6=0
  5. algebra

    1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic equation has roots 7 and -2/3? answer=A A.2x^2-11x-21=0 B.3x^2-19x-14=0 C.3x^2+23x+14=0 D.2x^2+11x-21=0 3)To solve 4x^2-28x+49=25 by using the square root
  6. Algebra 2

    find all the possible rational roots of g(x)=2x^4+6x^3-11x+8
  7. Maths

    How to find all roots of"x³-7x²+11x-5=0"
  8. math

    The equation that has the roots 1, 2, 3 is: (a) x3 + 6x2 – 11x + 6 (b) x3 – 6x2 + 11x – 6 * (c) x3 + 6x2 + 11x + 6 (d) x3 – 6x2 – 11x – 6 how ?
  9. math

    find the sum and product of the roots of the equation 5x^2+11x-3=0 ?
  10. Math

    find the roots of x3+6x2+11x+6=0 what is the formula and answer how to solve this ??

More Similar Questions